Beyond English and Bahasa: Exploring the Pedagogical Functions of Code-Switching in Multilingual EFL Contexts - Sri Dewi Mulyani; Delfi, Syofia; Jismulatif, Jismulatif (REiLA : Journal of Research and Innovation in Language, 2024)
Code-switching, the alternation between two or more languages, is a prevalent yet underexplored phenomenon in multilingual EFL classrooms in Indonesia. This study investigates the functional roles of code-switching employed by English teachers at SMAN 1 Rambah, emphasizing its pedagogical and managerial contributions. Addressing gaps in prior research, which primarily focus on English and Bahasa Indonesia, this study uniquely incorporates the role of local languages such as Mandailing and Malay. Employing a qualitative case study design, data were collected through classroom observations, video recordings, and semi-structured interviews with two experienced English teachers. The analysis revealed five key functions of code-switching: explaining complex concepts, translating vocabulary, repeating for reinforcement, checking comprehension, and managing classroom interactions. These functions significantly enhance students' understanding, engagement, and overall learning experiences. However, excessive reliance on code-switching may impede immersive English language practice, presenting a pedagogical challenge. The findings underscore the importance of balancing code-switching with English immersion to optimize learning outcomes. This study extends the theoretical discourse on multilingual pedagogy by highlighting the strategic integration of local languages into EFL teaching. Implications include fostering a more inclusive and culturally responsive language education framework, which accommodates linguistic diversity while promoting English proficiency. These insights contribute to the global discourse on multilingual education, particularly in settings where linguistic and cultural diversity intersects with educational objectives.